Evaluation of Heavy Metals in Blood Samples of Both Males and Females of Different Age Groups from Urban Areas of Faisalabad - Hussain, Naqi; Zaheer, Muhammad; Nawaz Chaudhry, Muhammad; Rahman, Salma; Sherazi, Nomia (Asian Journal of Chemistry, 2011)
The role of minerals is very important in carrying out vital activities of human body but due to paradoxical properties of heavy metals their presence in elevated quantities may cause toxicity. Present study has been carried out to evaluate the concentration of lead, copper, cadmium and chromium in blood samples of both males and females of different age groups from urban areas of Faisalabad by using atomic absorption spectrophotometer. The statistical analysis of present study revealed that concentration of heavy and trace metals in both males and females is independent of age and sex except linear progression in blood lead and cadmium levels with age was observed in males (P < 0.05). It is concluded from the this research that the overall high concentrations of heavy and trace metals were observed in all the subjects of urban areas indicating high concentrations of these metals in the environment.